Osmotic dehydration of honeydew (Cucumis melo L. var inodorus) using high power ultrasonic treatment - Gheybi, Farzad (2012)
Osmotic dehydration as an interesting method in food industry needs to be improved by complimentary methods to be more economical and effective. The objectives of this study were to investigate on osmotic dehydration of honeydew (Cucumis melo var. inodorus), to optimize the process and to investigate the effects of high power ultrasonic on the osmotic dehydration of the fruit. The effects of storage of fruits for 15 days on mass transfer parameters during osmotic dehydration in a fix temperature (50 °C), concentration (50 %), size (2.0 cm) and agitation (10000 Re) and also effect of different processing factors of temperature (30-60 °C), concentration (20-70 %) of osmotic solution, size (1-3 cm) of fruit sample and agitation (0-11748.26 Re) on the osmotic dehydration of honeydew were investigated. Results showed that 15 days storage of fruit affect the mass transfer parameters of osmotic dehydration of honeydew. Results also indicated that the most important factors in osmotic dehydration of honeydew were concentration of osmotic solution and size. Meanwhile, the optimized level of process parameters of temperature (40-60°C), concentration (45-65 %), agitation (5000-15000 Re) and time (2-4 h) was determined by using response surface method. the optimized process,considering economical, industrial and quality related constraints, was obtained at temperature of 57 oC, concentration of 65 %, time of 2.76 hours and agitation of 14999.80 Re. Ultrasonic treatment was applied to improve mass transfer rate in osmotic dehydration. The use of ultrasound treatment increased the water diffusivity of fruit, leading to a shorter dehydration time. Ultrasonic treatment during osmotic dehydration affected the cell structure of honeydew. The voids on the surface of the fruit and the microscopic channels on cell structure were responsible for the increase in water diffusivity. Based on the results derived from the ultrasonic regime of osmotic dehydration, short period of sonication time and rest time were needed during osmotic dehydration. Modelling and kinetic study of osmotic dehydration of honeydew was carried out using Azuara’s and Magee’s, Page’s, Logarithmic and Crank’s models. Azuara’s and Magee’s models were better to be used as compared to Page’s,Logarithmic and Crank’s models because they can fit the solid gain (SG) data more accurately and they turn out to be good enough for fitting water loss (WL) data. Meanwhile, based on the results from the study on the proposed model, the model could therefore be used to predict the equivalent WL and WL in any processing time by using the process parameters. It can be concluded that storage time of honeydew affect on mass transfer parameters during osmotic dehydration and agitation of turbulent level (Re>10000) affect on mass transfer significantly. Also ultrasonic treatment can increase mass transfer (5%) during osmotic dehydration. The WL and infinite WL can be predicted proposed model that consider processing factors. Osmotic dehydration of honeydew can be enhanced by increasing agitation level to turbulent level and applying ultrasonic treatment.